Pengaruh Penghindaran Pajak, Kualitas Audit, Intensitas Modal, dan Leverage Terhadap Biaya Utang - Kristanti, Ribka Angelina; Hasanah, Nuramalia; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The purpose of this study is to ascertain how tax avoidance, audit quality, leverage, and capital intensity affect cost of debt. With a total observation sample of 170, this study analyzes secondary data from financial reports in the energy and raw materials sectors (mining companies) listed on the Indonesia Stock Exchange (BEI) for the 2018–2022 timeframe. Purposive sampling is used in the sampling procedure, and panel data regression is analyzed using the Eviews 12 program. Therefore, the cost of debt is unaffected by tax avoidance, capital intensity, or leverage. Cost of Debt is negatively impacted by audit quality.